2008
DOI: 10.1007/bf03217475
|View full text |Cite
|
Sign up to set email alerts
|

Suggestion for a theoretical model for secondary-tertiary transition in mathematics

Abstract: One of most notable features of existing body of research in transition seems to be the absence of a theoretical model. The suggestion we present in this paper-to view and understand the high school to university transition in mathematics as a modern-day rite of passage-is an attempt at defining such framework. Although dominantly reflecting North-American reality, we believe that the model could be found useful in other countries as well. Let us emphasize that our model is not new in the sense that it recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 8 publications
0
46
0
2
Order By: Relevance
“…The amount of research in mathematics education at the tertiary level is still modest (Selden & Selden, 2001), and very few studies have focused on the secondary tertiary transition (Clark & Lovric, 2008). However, it is not without its limitations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of research in mathematics education at the tertiary level is still modest (Selden & Selden, 2001), and very few studies have focused on the secondary tertiary transition (Clark & Lovric, 2008). However, it is not without its limitations.…”
Section: Resultsmentioning
confidence: 99%
“…Research has found that such transitional issues between secondary and tertiary mathematics education are common place and involve a whole spectrum of problems and difficult situations (Kajander & Lovric, 2005;Clark & Lovric, 2008). Guzman et al (1998, p.748) identified this transition point as "a major stumbling block in the teaching of mathematics".…”
Section: Insert Table 1: Project Maths Implementation Timelinementioning
confidence: 99%
“…Additionally, De Guzmán et al (1998) refer to the competitiveness that is created occasionally among students in the lecture theatres and which can create a feeling of discomfort. Furthermore, when students enter university, they are unaware of numerous aspects of university life and the ways in which academic requirements will change from those they were used to at school (Clark and Lovric 2008). Thomas and Klymchuk (2012) argue that one of the biggest problems that students encounter with the move to university is the freedom that they acquire.…”
Section: Changes In the Didactical And Sociological/cultural Aspectsmentioning
confidence: 99%
“…The dramatic character is depicted in the word "abstraction shock", used by some authors since there is a notable difference between mathematics taught at school and at university. Clark and Lovric (2008) understand secondary-tertiary transition in mathematics as a rite of passage (a well-studied anthropological concept), an initi-ation into a new world. As such, they describe the three stages of transition from high school to university as follows:…”
Section: Secondary-tertiary Transitionmentioning
confidence: 99%